Pemanfaatan Multimedia Berbasis Cloud (google site) untuk Optimalisasi Pembelajaran IPAS: Studi Empiris Peningkatan Kognitif dan Afektif Siswa Sekolah Dasar di Kota Madiun - Nurhayati; Sudarmiani; Yudi Hartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student motivation and learning outcomes in Science and Social Studies (IPAS) at the elementary school level are often caused by conventional teaching methods and a lack of interactive media. This study aims to analyze the use of cloud-based multimedia via Google Sites in optimizing the cognitive and affective aspects of 6th-grade students at SDN 01 Mojorejo, Madiun. This study is a Classroom Action Research (CAR) using the Kemmis & McTaggart model, conducted in two cycles. The subjects were 23 students. Data were collected through learning motivation observations (ARCS model), learning outcome tests, and documentation, which were then analyzed using descriptive qualitative and quantitative methods. Findings showed significant improvements in each cycle. The average student motivation increased from 1.75 (pre-cycle) to 3.12 (Cycle I) and reached 4.42 (Cycle II) with 86.96% classical completeness. Similarly, the average cognitive learning outcomes rose from 55.22 (pre-cycle) to 69.35 (Cycle I) and reached 86.74 (Cycle II) with 91.30% classical completeness. The use of Google Sites multimedia is effective in increasing motivation and IPAS learning outcomes. The integration of cloud-based technology provides an interactive and contextual learning experience aligned with the implementation of the Merdeka Curriculum in the digital era.